Analysis Of Determinant Factors Influencing Purchase Intention Of Generation Z On Korean Skin Care Products In Batam City - Suyanti Suyanti; Immanuel Zai (UNIVED Press, 2025)
By using the TRA perspective, this study aims to analyze the influence of brand image, brand awareness, celebrity endorsement, eWOM, and perceived quality on the purchase intention of generation z towards Korean skin care brands, mediated by brand trust. The study uses a quantitative cross-sectional method and analyzes data using Smart PLS-SEM, which is suitable for more complex models. The results show that the relationship between brand image, celebrity endorsement, brand awareness, and perceived quality towards brand trust are significantly positive impact and brand trust successfully mediated brand image, celebrity endorsement, brand awareness and perceived quality on purchase intention. Meanwhile, eWOM do not have significant impact on brand trust.